A translationally relevant thromboembolic stroke model for the study of secondary hemorrhage after thrombolysis in rats - Sun, Li; Zhou, Wei; Heiland, Sabine; Marti, Hugo; Veltkamp, Roland (Brain research, 2011)
Secondary hemorrhage after thrombolysis in ischemic stroke is an important complication, which has been difficult to study in preclinical disease models. We have established and characterized a model of thromboembolic middle cerebral artery occlusion in rats. Advantages of this model include a very low rate of spontaneous recanalization and good reperfusion after intravenous thrombolysis with recombinant tissue plasminogen activator (rt-PA). In vivo T2* MR imaging and postmortem assays were used for quantification of secondary brain hemorrhage. In our protocol, 12 thrombin-induced autologous blood clots are injected into the internal carotid artery. No spontaneous reperfusion occurs in the first 24h. However, injection of rt-PA 2 or 4h thereafter leads to reperfusion of the MCA territory consistent infarcts, increased blood-brain barrier permeability, and secondary hemorrhage. Remarkably, clinically important factors known to affect the extent and likelihood of secondary hemorrhage such as hypertension and delayed onset of thrombolysis also increase hematoma size in the model. Thus, the model may serve to investigate the pathophysiology of thrombolysis-induced hemorrhage in thromboembolic ischemia as well as potential adjunctive therapies to prevent this complication.
Online verfügbar 23 Oktober 2010
Gesehen am 26.10.2022